Outcomes of cinacalcet withdrawal in Australian dialysis patients. Issue 1 (24th January 2019) - Ruderman, Irene; Holt, Stephen G.; Kirkland, Geoffrey S.; Maslen, Sophie; Hawley, Carmel M.; Oliver, Veronica; Krishnasamy, Rathika; Gray, Nicholas A.; Talaulikar, Girish S.; Nelson, Craig L.; Rajaram, Yogeshwar; Gock, Hilton; et al.
Abstract: Background: Secondary hyperparathyroidism (SHPT) in chronic kidney disease is associated with cardiovascular and bone pathology. Measures to achieve parathyroid hormone (PTH) target values and control biochemical abnormalities associated with SHPT require complex therapies, and severe SHPT often requires parathyroidectomy or the calcimimetic cinacalcet. In Australia, cinacalcet was publicly funded for dialysis patients from 2009 to 2015 when funding was withdrawn following publication of the EVOLVE study, which resulted in most patients on cinacalcet ceasing therapy. We examined the clinical and biochemical outcomes associated with this change at Australian renal centres. Aim: To assess changes to biochemical and clinical outcomes in dialysis patients following cessation of cinacalcet. Methods: We conducted a retrospective study of dialysis patients who ceased cinacalcet after August 2015 in 11 Australian units. Clinical outcomes and changes in biochemical parameters were assessed over a 24‐ and 12‐month period, respectively, from cessation of cinacalcet. Results: A total of 228 patients was included (17.7% of all dialysis patients from the units). Patients were aged 63 ± 15 years with 182 patients on haemodialysis and 46 on peritoneal dialysis. Over 24 months following cessation of cinacalcet, we observed 26 parathyroidectomies, 3 episodes of calciphylaxis, 8 fractures and 50 deaths. Eight patients recommenced cinacalcet, meeting criteria under a special access scheme. Biochemical changes from baseline to 12 months after cessation included increased levels of serum PTH from 54 (interquartile range 27–90) pmol/L to 85 (interquartile range 41–139) pmol/L ( P < 0.0001), serum calcium from 2.3 ± 0.2 mmol/L to 2.5 ± 0.1 mmol/L ( P < 0.0001) and alkaline phosphatase from 123 (92–176) IU/L to 143 (102–197) IU/L ( P < 0.0001). Conclusion: Significant increases in serum PTH, calcium and alkaline phosphatase occurred over a 12‐month period following withdrawal of cinacalcet. Longer‐term follow up will determine if these biochemical and therapeutic changes are associated with altered rates of parathyroidectomies and cardiovascular mortality and morbidity.